PELAKSANAAN DIET MAHASISWI DI FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS ABDURRAB - Yulia Febrianita; Rada Isdayani; Roni Saputra (STIKes Al-Insyirah Pekanbaru, 2022)
Diet is a familiar thing for women in today's modern era. Diet is defined as the activity of restricting and controlling the food that will be eaten with the aim of reducing and maintaining weight (Hawks, 2012). This study aims to determine the description of the implementation of the diet carried out by college students. This research method is quantitative descriptive with a questionnaire measuring tool that contains 20 questions that contain the assessment of the implementation of the diet. The sample of this study was 245 female students from the Faculty of Medicine and Health Sciences, Abdurrab University, Pekanbaru. The results showed as many as 131 people (53.5%) of respondents adopted an appropriate diet. While as many as 114 people (46.5%) of respondents implemented an inappropriate diet. Based on the findings it is recommended that female students are given information about eating patterns and appropriate diets for female students to reduce the incidence of deviant eating behavior.